2010
DOI: 10.5009/gnl.2010.4.s1.s82
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Oncological Therapy Comprising Stents, Brachytherapy, and Regional Chemotherapy for Cholangiocarcinoma

Abstract: Background/Aims: To prospectively evaluate our palliative management of unresectable cholangiocarcinoma (CC) treated with tailored multimodal oncological therapy. Methods: Between January 2005 and January 2010, 50 consecutive patients with unresectable CC and jaundice were palliated with percutaneous drainage. Forty-three patients underwent metallic-stent implantation followed by brachytherapy. Patients were divided into two arms: the intra-arterial chemotherapy arm (IA arm, n=17) consisted of patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…However, the difference did not reach statistical significance (Table 4). In a prospective study by Andra sina et al [30], favorable prognoses were achieved by a complex tailored oncological therapy comprising stent, brachytherapy, and chemotherapy. Another retrospective analysis revealed that, for unresectable hilar CC, a multimodal approach combining percutaneous stenting with radiotherapy and chemotherapy is an effective alternative to palliative surgery [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference did not reach statistical significance (Table 4). In a prospective study by Andra sina et al [30], favorable prognoses were achieved by a complex tailored oncological therapy comprising stent, brachytherapy, and chemotherapy. Another retrospective analysis revealed that, for unresectable hilar CC, a multimodal approach combining percutaneous stenting with radiotherapy and chemotherapy is an effective alternative to palliative surgery [31].…”
Section: Discussionmentioning
confidence: 99%
“…For the future, complex multimodal concepts are the key to further improve progression-free and overall survival as well as the quality of life in patients with CC in different stages. For example, Andrasina et al [44] presented an interdisciplinary approach for symptomatic irresectable ICC and ECC by means of biliary stent implantation, brachytherapy, and chemotherapy. After successful biliary drainage (metallic stent placement and intraluminal brachytherapy), patients were assigned either to an arm with transarterial chemotherapy (for patients with hypervascular tumors) or to an arm with intravenous chemotherapy (for patients with hypovascular tumors).…”
Section: Discussionmentioning
confidence: 99%
“…In the first review, Ray et al [41] included 16 studies with a total of 542 patients undergoing chemotherapy-based transarterial therapy, whereas in all studies - except in the study by Andrasina et al [44] - repetitive TACE was performed in a typical fashion with transarterial injection of one or more chemotherapeutic agents and one or more embolic agents [41]. After pooling, the tumor control, severe toxicity, 30-day mortality, and 1-year overall survival rates were 76.8, 18.9, 0.7, and 58.0%, respectively.…”
Section: Locoregional Therapymentioning
confidence: 99%
“…The primary advantage of intraluminal brachytherapy over external beam radiotherapy is that higher doses of irradiation can be given without damaging adjacent normal tissues [58] . This procedure is usually done through PTBD route, preferably after metallic stent placement.…”
Section: Intra-biliary Palliative Therapymentioning
confidence: 99%